ONLINE BUYING AND SELLING FROM THE PERSPECTIVE OF MAQASID SHARIAH - Umi Khusnul Khotimah (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2023)
Maqasid Syariah encourages the economic empowerment of Muslims. Online buying and selling transactions can provide opportunities for Muslim entrepreneurs to develop and compete in the global market, thereby achieving this goal of economic empowerment. Overall, online buying and selling transactions can be a means to achieve the goals of Maqasid Syariah, as long as they are carried out with integrity, fairness and comply with the principles of Islamic law. Good online business practices must align with Islamic values ​​and moral goals and contribute to the overall welfare of society. Research focus The online buying and selling transaction process is seen from Maqasid sharia. Research Method This research is a qualitative descriptive research. In this qualitative descriptive research, researchers here use library research to look for information through books, magazines, newspapers and other literature to form a theoretical basis. This research is also to examine written sources such as scientific journals, reference books, literature, encyclopedias, scientific essays, scientific works and other sources either in written form or in digital format that are relevant and related to the object being researched. The object of this research study is in the form of texts or writings that describe and explain the online shop business/enterprise that is mushrooming in Indonesia. The results of this research are 1) maintaining religion, in online buying and selling transactions you must have good intentions and the goods being sold match the picture and what was sent. 2) Maintain Product Quality Ensure that the product or service you purchase is safe to use. When possible, read reviews and do research on the product, especially if it concerns health and safety. Dangerous Product Monitoring If you sell products or services that could impact consumer health or safety, ensure they meet applicable safety and regulatory requirements. Respect for Consumer Rights Make sure you understand consumer rights in online transactions, including the right to return defective or unsuitable goods. Make sure that sellers respect these rights. 3) maintain common sense, avoid rash actions, don't rush to make decisions. If you feel pressured or pushed to make a transaction immediately, you should be careful and consider your decision carefully. 4) maintaining lineage Maintaining lineage (descendants) in online buying and selling transactions refers to the practice of maintaining business relationships with integrity and honesty as well as upholding moral and ethical principles in all aspects of online business. 5) maintain honest assets towards oneself and the goods being sold.